Integrating animal cruelty exposure into person-centered models of childhood adversity: latent classes and associations with depression, anxiety, and stress - McDonald, Shelby E.; Tomlinson, Camie; Nicotera, Nicole; Kogan, Lori R.; Abell, Tiarra; Ford, Jada; Jafarian, Sohaila; Girish, Gehena; Rodriguez, Lydia Soto; Bright, Charlotte L. (Frontiers in Psychiatry, 2025)
BackgroundAnimal cruelty is a recognized correlate of interpersonal violence within family systems, yet children’s exposure to this form of harm remains absent from most standardized assessments of childhood adversity. Guided by the Dimensional Model of Adversity and Psychopathology, this study examined the co-occurrence of exposure to animal cruelty with other threat-related adverse childhood experiences (ACEs) and how these patterns relate to adult mental health.MethodsOur sample included 1,072 U.S. adults recruited online through Prolific, a licensed participant recruitment firm, using its representative U.S. sample option. Participants reported on childhood experiences of emotional abuse, physical abuse, sexual abuse, exposure to domestic violence, and exposure to animal cruelty, along with current symptoms of depression, anxiety, and stress. Latent class analysis identified subgroups based on adversity profiles. Associations between class membership and sociodemographic factors were examined, and differences in mental health outcomes across classes were estimated adjusting for these covariates.ResultsA three-class model best fit the data: low adversity (29.6%), interpersonal violence only (34.8%), and interpersonal violence and animal cruelty (35.6%). Membership in the latter was more likely among younger participants, those with a minoritized gender modality, those with a minoritized sexual orientation, and Hispanic or Black individuals compared to white participants. The class interpersonal violence and animal cruelty reported the highest depression, anxiety, and stress scores, followed by the interpersonal violence only group, with the low adversity group reporting the lowest scores (all ps <.001; moderate-to-large effects).ConclusionFuture research should test whether including animal cruelty in person-centered models of adversity improves identification of high-risk subgroups, and explore how such inclusion can inform multispecies approaches to violence prevention and intervention.